A Study Survey of Awareness of Jordanian Chemists about Chemical Hazards - Waed R Alahmad; Tala H. Sasa; Nawal H Bahtiti; Ahmed Abu-Rayan (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study is an attempt to identify the level of awareness of safety measures practiced in the survey wasconducted between September and December 2020 among chemists graduated in Jordan in several workingsectors (teaching, Laboratory work and in manufactures). A total of 245 eligible subjects were asked toparticipate in the study. The majority were females (71.0%), their ages ranged from 18 to 40 years, and mostof them were between 18-22 (62.9%). As for educational qualifications, 65% were students. 77.1% of themhad a good knowledge of chemistry. Most of the accidents were in the laboratory by females (68%), 78%of the accidents were by females in the household. The age of 18-22 (58.9%) caused most of the accidentsin the laboratory. Also, the age of 18-22 (69.9%) caused most of the accidents in the household. 55.5% oflaboratory accidents were from students. As result females and students were the major reason for chemicalaccidents. There is no significant difference in the average attitude towards chemical safety by age. There isno significant difference in the average attitude towards chemical safety as per education.